Psychological issues in pediatric obesity - Kalra, Gurvinder (Medknow Publications & Media Pvt Ltd, 2012)
Pediatric obesity is a major health problem and has reached epidemiological proportions today. The present paper reviews major psychological issues in pediatric obesity from a developmental perspective. Research and literature has shown that a number of developmental, family, maternal and child factors are responsible in the genesis of pediatric obesity. Family food habits, early developmental lifestyle of the child, parenting, early family relationships and harmony all contribute towards the growth and development of a child. The present review focuses on the role of developmental psychological factors in the pathogenesis of pediatric obesity and highlights the developmental factors that must be kept in mind when evaluating a case of pediatric obesity.